Yellow Sweet Potato (Ipomea batatas L.) And Red Bean (Phaseolus vulgaris L.) Composite Flour Formulation For Biscuit Making - Frische Christin Gigiringi; Erny J. N. Nurali; Maya M. Ludong (Sam Ratulangi University, 2022)
Biscuit is a kind of snack that have a relatively texture. Yellow sweet potato and red bean as local foods were used as composite flour for biscuit making. This aims of this research were to (1) analyze the nutrional content (moisture, ash, fat, protein, carbohydrate, crude fiber and total calories) of yellow sweet potato and red bean composite flour biscuits. (2) evaluate the level of preference for composite flour biscuits with yellow sweet potato and red bean. This research used a completely randomized design (CRD) with sweet potato flour and red bean flour treatments, namely A (50% : 50%), B (60% : 40%), C (70% : 30%), D (80% : 20%). The results of this research is stated that nutritional content of the yellow sweet potato and red bean composite flour biscuits had an average value of moist (10% - 13%), ash content (1% - 2%), fat content (7.06% - 8.73%), protein content (6.5% - 8.45%), carbohydrates (67.8% - 74.9%), crude fiber (3.74% - 4.02%) and total calories (383,57 kcal - 392 kcal) . The results of the sensory test of the level of preference for color 5.21 - 5.48 (slightly like), aroma 5.36 - 5.68 (slightly like-like), taste 5.41 - 6.02 (slightly like - like), texture 4.81 - 5.77 (slightly like - like). Keywords: Biscuits, Yellow Potato Flour, Red Bean Flour. Abstrak Biskuit merupakan makanan ringan yang memiliki tekstur relatif renyah bila dipatahkan dan memiliki potongan yang bertekstur padat. Dalam penelitian ini menggunakan tepung ubi jalar kuning dan tepung kacang merah sebagai bahan pangan lokal yang dapat memberikan nilai gizi pada biskuit. Penelitian ini bertujuan untuk (1) menganalisis kandungan gizi (kadar air, kadar abu, kadar lemak, kadar protein, kadar karbohidrat, kadar serat kasar dan total kalori) biskuit tepung komposit ubi jalar kuning dan kacang merah. (2) mengevaluasi tingkat kesukaan produk biskuit tepung komposit ubi jalar kuning dan kacang merah. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan perlakuan tepung ubi jalar kuning dan tepung kacang merah, yaitu A (50% : 50%), B (60% : 40%), C (70% : 30%), D (80% : 20%). Hasil kandungan gizi dari biskuit tepung komposit ubi jalar kuning dan kacang merah memiliki nilai rata-rata kadar air (10% - 13%), kadar abu (1% - 2%), kadar lemak (7,06% - 8,73%), kadar protein (6,5% - 8,45%), karbohidrat (67,8% - 74,9%) , serat kasar (3,74% - 4,02%) dan kalori (383,57 kkal - 392 kkal). Hasil uji sensoris tingkat kesukaan terhadap warna 5,21 - 5,48 (agak suka), aroma 5,36 - 5,68 (agak suka - suka), rasa 5,41 - 6,02 (agak suka - suka), tekstur 4,81 - 5,77 (agak suka - suka). Kata kunci: Biskuit, Tepung Ubi Jalar Kuning, Tepung Kacang Merah